2016
DOI: 10.3389/fphys.2016.00037
|View full text |Cite
|
Sign up to set email alerts
|

The Path to Exhaustion: Time-Variability Properties of Coordinative Variables during Continuous Exercise

Abstract: The aim of this study was to detect qualitative changes in the structure of coordinative variable (elbow angle) fluctuations during a quasi-isometric exercise performed until exhaustion. Seven physical education students performed a quasi-isometric arm-curl exercise holding an Olympic bar (weight: 80% 1RM) with an initial elbow flexion of 90° three times over a period of 4 weeks. They were encouraged to persist, even if the elbow angle was lost, until the fatigue-induced spontaneous termination point (FISTP). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
57
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(64 citation statements)
references
References 27 publications
6
57
0
1
Order By: Relevance
“…This constant value of the load can be interpreted as a stable fixed point—which losses its stability due to the fatigue. Similar loss of stability in a quasi-isometric arm-curl exercise reflected by the increase of low-frequency fluctuations is observed in [25]. …”
Section: Visualization Of the Load And The Recovery Processessupporting
confidence: 76%
“…This constant value of the load can be interpreted as a stable fixed point—which losses its stability due to the fatigue. Similar loss of stability in a quasi-isometric arm-curl exercise reflected by the increase of low-frequency fluctuations is observed in [25]. …”
Section: Visualization Of the Load And The Recovery Processessupporting
confidence: 76%
“…Discussion and conclusion: Implications of measuring team dynamics for understanding collective developmental systems in sports will be discussed with further analysis on our preliminary data sets. Introduction: Changes in the time-variability properties of a kinematic variable during a quasi-isometric exercise performed until exhaustion has been recently revealed (Vázquez et al, 2016). These changes, presumably informing about the state of the temporal couplings between the neuromuscular system's components, provided information about the dynamic mechanisms that lead to exhaustion.…”
Section: Resultsmentioning
confidence: 99%
“…The type of variability reflects the degree of coupling among the system components and its qualitative reorganisation. Vázquez et al 34 have shown that the change in the cooperative behaviour of neuromuscular components as fatigue develops is manifested through the changes in the time variability properties of the kinematic coordinative variable. A small perturbation (eg, pain sensation or imbalance) when the neuromuscular system is unstable, that is, close to exhaustion, can suddenly provoke the task disengagement.…”
Section: Connectivitymentioning
confidence: 99%
“…Sports injuries arising after relatively long resting periods, such as those that occur during preseason, 60 may thus be explained by a mismatch between the performance that the athlete tries to achieve and his/her current capabilities. The lack of cooperation among biological levels reduces the synergistic possibilities of maintaining MSS stability 34 and should be carefully considered when designing training programmes. According to the antagonistic effects over different timescales pointed out here, it is likely not the increase or decrease of training workloads per se that affects MSS susceptibility to injuries, 54 but rather appropriate workload provided relative to timings.…”
Section: Effects Of Workloads At Different Timescalesmentioning
confidence: 99%